Validation of a parent-proxy quality of life questionnaire for paediatric chronic cough (PC-QOL). Issue 9 (30th August 2010) - Newcombe, Peter A; Sheffield, Jeanie K; Juniper, Elizabeth F; Petsky, Helen L; Willis, Carol; Chang, Anne B
Abstract : Background: Quality of life (QOL) measures are an important patient-relevant outcome measure for clinical studies. Currently there is no fully validated cough-specific QOL measure for paediatrics. The objective of this study was to validate a cough-specific QOL questionnaire for paediatric use. Method: 43 children (28 males, 15 females; median age 29 months, IQR 20–41 months) newly referred for chronic cough participated. One parent of each child completed the 27-item Parent Cough-Specific QOL questionnaire (PC-QOL), and the generic child (Pediatric QOL Inventory 4.0 (PedsQL)) and parent QOL questionnaires (SF-12) and two cough-related measures (visual analogue score and verbal category descriptive score) on two occasions separated by 2–3 weeks. Cough counts were also objectively measured on both occasions. Results: Internal consistency for both the domains and total PC-QOL at both test times was excellent (Cronbach alpha range 0.70–0.97). Evidence for repeatability and criterion validity was established, with significant correlations over time and significant relationships with the cough measures. The PC-QOL was sensitive to change across the test times and these changes were significantly related to changes in cough measures (PC-QOL with: verbal category descriptive score, rs =−0.37, p=0.016; visual analogue score, rs =−0.47, p=0.003). Significant correlations of the difference scores for the social domain of the PC-QOL and the domain and total scores of the PedsQL were also noted (rs =0.46, p=0.034). Conclusion: The PC-QOL is a reliable and valid outcome measure that assesses QOL related to childhood cough at a given time point and measures changes in cough-specific QOL over time.